2012
DOI: 10.5152/etd.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cervical Culture Results in Preterm Labor and Premature Rupture of Membranes

Abstract: GirişPreterm eylem tüm dünyada yeni doğan ölümleri ve konjenital anomalilerle ilişkilidir (1). Perinatal mortalitenin önde gelen sebebi olmasının yanında ortaya çıkan uzun vadeli ve ağır komplikasyonlar ve artan tedavi maliyetleri, konunun önemini artırmaktadır (2). Preterm doğan bebeklerde görme ve işitme bozuklukları, kronik akciğer hastalığı, serebral palsi ve gelişme geriliği daha sık görülmektedir (1). Perinatal morbidite ve mortalite özellikle 32. haftadan önce doğan bebeklerde görülür. Prematürite ile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
3
2
0
Order By: Relevance
“…38 In a study conducted in Turkey, it was found that the colonization of microorganisms is four times higher in women with PTB than in pregnant women without PTB, indicating a relationship between colonization and PTB. 21 Our research findings are similar to the findings of the literature in this respect. 12,21,38 It has been stated that VD performed for genital hygiene causes PTB.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…38 In a study conducted in Turkey, it was found that the colonization of microorganisms is four times higher in women with PTB than in pregnant women without PTB, indicating a relationship between colonization and PTB. 21 Our research findings are similar to the findings of the literature in this respect. 12,21,38 It has been stated that VD performed for genital hygiene causes PTB.…”
Section: Discussionsupporting
confidence: 91%
“…21 Our research findings are similar to the findings of the literature in this respect. 12,21,38 It has been stated that VD performed for genital hygiene causes PTB. It has been reported that 50.2%-68.4% of women in Turkey perform VD.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations